Understanding health system resilience in responding to COVID-19 pandemic: experiences and lessons from an evolving context of federalization in Nepal - Shophika Regmi; Maria Paola Bertone; Prabita Shrestha; Suprich Sapkota; Abriti Arjyal; Tim Martineau; Joanna Raven; Sophie Witter; Sushil Baral (BMC, 2024)
Abstract Introduction The COVID-19 pandemic has tested the resilience capacities of health systems worldwide and highlighted the need to understand the concept, pathways, and elements of resilience in different country contexts. In this study, we assessed the health system response to COVID-19 in Nepal and examined the processes of policy formulation, communication, and implementation at the three tiers of government, including the dynamic interactions between tiers. Nepal was experiencing the early stages of federalization reform when COVID-19 pandemic hit the country, and clarity in roles and capacity to implement functions were the prevailing challenges, especially among the subnational governments. Methods We adopted a cross-sectional exploratory design, using mixed methods. We conducted a desk-based review of all policy documents introduced in response to COVID-19 from January to December 2020, and collected qualitative data through 22 key informant interviews at three tiers of government, during January-March 2021. Two municipalities were purposively selected for data collection in Lumbini province. Our analysis is based on a resilience framework that has been developed by our research project, ReBUILD for Resilience, which helps to understand pathways to health system resilience through absorption, adaptation and transformation. Results In the newly established federal structure, the existing emergency response structure and plans were utilized, which were yet to be tested in the decentralized system. The federal government effectively led the policy formulation process, but with minimal engagement of sub-national governments. Local governments could not demonstrate resilience capacities due to the novelty of the federal system and their consequent lack of experience, confusion on roles, insufficient management capacity and governance structures at local level, which was further aggravated by the limited availability of human, technical and financial resources. Conclusions The study findings emphasize the importance of strong and flexible governance structures and strengthened capacity of subnational governments to effectively manage pandemics. The study elaborates on the key areas and pathways that contribute to the resilience capacities of health systems from the experience of Nepal. We draw out lessons that can be applied to other fragile and shock-prone settings.